Skin-Interfaced Therapeutic Patches for Wound Fluid Management and Transdermal Drug Delivery - Han, Dongjun; Kim, Donghyun; Lee, Haram; Park, Dong-Wook; Kwak, Sung Soo; Kim, Joohee (Wiley-Blackwell, 2026)
Delayed or non-healing wounds remain a considerable medical challenge owing to infection-related complications. Consequently, promoting wound healing through effective dressings and transdermal drug delivery systems is crucial. However, current approaches are hindered by complex drug formulations or dependence on bulky external equipment, limiting their practicability and patient convenience. To overcome these limitations, this study presents a skin-interfaced therapeutic patch that integrates wound fluid management with a transdermal drug delivery system. The wound fluid management component consists of a microfluidic channel and a chamber combined with a hydrogel film, which collects and preserves wound fluid rich in wound-healing factors, thereby maintaining optimal hydration and providing a protective barrier. The transdermal drug delivery system utilizes an iontophoresis module incorporating bio-derived DNA polymers that promote tissue regeneration, enabling the direct and efficient delivery of therapeutic agents through the skin. The multifunctional patch is validated via in vitro and in vivo studies, thereby demonstrating accelerated and robust tissue regeneration.